2017 IEEE/ACM 25th International Conference on Program Comprehension (ICPC) 2017
DOI: 10.1109/icpc.2017.20
|View full text |Cite
|
Sign up to set email alerts
|

Software Engineers' Information Seeking Behavior in Change Impact Analysis - An Interview Study

Abstract: Software engineers working in large projects must navigate complex information landscapes. Change Impact Analysis (CIA) is a task that relies on engineers' successful information seeking in databases storing, e.g., source code, requirements, design descriptions, and test case specifications. Several previous approaches to support information seeking are task-specific, thus understanding engineers' seeking behavior in specific tasks is fundamental. We present an industrial case study on how engineers seek infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Another concept related to traceability is change management [19]-i.e., the idea that when a software artifact is changed, all associated artifacts need to be identified and updated accordingly. The responsibility for this task is often delegated to the development team, and its complexity is affected by the already available traceability links.…”
Section: Software Artifacts Traceabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Another concept related to traceability is change management [19]-i.e., the idea that when a software artifact is changed, all associated artifacts need to be identified and updated accordingly. The responsibility for this task is often delegated to the development team, and its complexity is affected by the already available traceability links.…”
Section: Software Artifacts Traceabilitymentioning
confidence: 99%
“…The responsibility for this task is often delegated to the development team, and its complexity is affected by the already available traceability links. In their case study, Borg et al found that developers prefer flexible forms of information rather than formal information, including traceability information, when dealing with changes [19].…”
Section: Software Artifacts Traceabilitymentioning
confidence: 99%
See 1 more Smart Citation